(untitled) (Journal of Organizational Psychology, 2020)
Several young Canadians have jobs that involve interaction with customers, placing them at risk for public-initiated sexual harassment. To date, research on sexual harassment has focused on outcomes of insider-initiated sexual harassment neglecting public-initiated harassment. Research on the former has shown that sexual harassment has negative outcomes for victims. In this study, I examined the relationship between public-initiated sexual harassment and mental health, physical health, and job satisfaction using hierarchical multiple regression. Participants were female, full-time university students. Results showed that sexual harassment initiated by members of the public was negatively related to employee mental health and physical well-being.